Performance Measure Of Some Subspace-Based Methods For Closed-loop System Identification. - A. Aziz, Muhammad Hilmi R.; Mohd Mokhtar, Rosmiwati (2010)
This paper presents some of the methods under subspace-based family to perform closed-loop system identification. Three methods have been observed; those are the ORT method, MOESP method and CCA method.